Como pode o homem escapar de si mesmo? uma leitura ficcional de Michel Foucault - Silva, Fernanda Gomes da (2019)
This research seeks to produce a perusal of Michel Foucault’s works – considered in its entirety – using as a gravitational axis what we call a critique of anthropological reason. At first, we look at Michel Foucault's retrospective analysis of his own work between 1978 and 1984, understanding this process as a rewriting the self movement. Then, we localize this gesture as a fictional procedure, similar to the ones Foucault employs as a methodological resource in his investigations. The doctoral dissertation pursues, therefore, to converge three uses of fiction: the one Foucault produces while reading himself; the one that works with fiction as a driving force of his elaborations; and, finally, the one we propose as we look over his thought. In doing so, we chose Immanuel Kant and Friedrich Nietzsche as privileged interlocutors. We work with the two philosophers to purpose a sort of “agonism” that Foucault has somehow preserved. This produces a between, a space that emerges from the tension between these two philosophies